GOODBYE, NEHRU: INDIAN FOREIGN POLICY UNDER GLOBALIZATION - Barbosa dos Santos, Fabio Luis (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This article analyses the trends of India’s foreign policy in recent years under the light of political and economic dynamics, with a focus in its regional surrounding. The text locates an inflection towards economic liberalization undertaken in the beginning of the 1990´s, and then moves on to the context of economic expansion in the 21st century. The achievements and limits of those processes are taken into consideration. In the political realm, as the legitimacy of the Indian National Congress (INC) was brought to check, so was its hegemony, in a process that has favored the rise of political agencies identified with hindu nationalism and communalism, such as the BJP. Overall, the hallmarks of Indian politics that prevailed since independence under leadership of the Congress Party are left behind: economic nationalism, secular politics, and international non-alignment. In this context, the broad orientation of Indian foreign policy also has changed. The text analyses the consequences of this inflection in the regional context, focusing the Neighbors first policy and the priority given to infrastructural connectivity with Southeast Asia (Look East and Act East policies), as well as the recent intensification of business in the African continent. Altogether, the expectations of an alternative civilizatory horizon in the context of the Cold War which has nurtured Nehruvian politics, has given place to a pragmatic rationality that accepts the United States leadership and as such, draws strategies adapting to the mercantile trends that typify globalisation.